Management of Phosphorus and Organic Matter on an Acid Soil in Jambi, Indonesia - SANTOSO D; J. PURNOMO; I GEDE PUTU WIGENA; . SUKRISTIYONUBOWO; R.D.B LEFROY (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2000)
A field experiment was conducted at Pauh Menang village, Jambi province, to assess crop and soil response to P fertilization, compare inorganic and organic sources of P, and assess the interactions between these sources. The experiment employed an incomplete factorial combination of six levels of inorganic P (0, 19, 38, 57, 76 and 95 kg P ha-1 as SP-6), two organic matters (FYM and stylo), and lime, laid out in a randomized complete block design with four replicates. The experiment was carried out over four seasons, from rainy season 1997/1998 until dry season 1999, however, the second crop failed due to severe drought. Under limed conditions, application of SP-36 at 38-kg P ha-1crop-1 increased soil P content. Repeated application of SP-36 resulted in accumulation of residual P and built up the P status of the soil well above 100 mg P kg-1 soil. The application of SP-36 in combination with OM, stylo or FYM, did not produce higher Colwell P contents in the soil compared with application of inorganic P alone. Grain yields of all corn crops increased significantly from about 0.5 to 3.5 t ha-1 with application of inorganic P at about 57 kg P ha-1. The amount of P fertilizer required to obtain 85% relative yield decreased from about 62 to 40 to 28 kg P ha-1 for crop 1 to crop 3 and to crop 4, providing evidence of the residual effect of P fertilization. The direct use of RP at 42.6 kg P ha-1crop-1 was less effective than the readily soluble inorganic SP-36 at 38 kg P ha-1 crop-1. Liming increased and maintained corn grain yields significantly. Application of OM as FYM or stylo in combination with SP-36 or RP did not resulted in synergistic interactions, with greater increases in yields. The introduction of an erect and fast growing stylo, Stylosanthes guyanensis cultivar CIAT 184, in the cropping system offers a good opportunity to improve fertility of acid soils. The high biomass yield of stylo, ranging from 0.8 to 4.9 t ha-1 per cutting, can be fed directly to cattle or sun-dried, ground and mixed with other materials to enrich feed concentrate. Widespread adoption of this legume would enhance cattle rearing, which in turn would produce more FYM as a source of organic P fertilizer .